2006
DOI: 10.1063/1.2202751
|View full text |Cite
|
Sign up to set email alerts
|

Magnetocaloric properties of Ni2Mn1−xCuxGa

Abstract: We present the magnetocaloric properties of the substituted Heusler alloy Ni2Mn1−xCuxGa, which shows a maximum magnetic entropy change of ΔSM≈−64J∕KgK=−532mJ∕cm3K at 308K for a magnetic field change ΔH=5T. The dependence of ΔSM on ΔH is approximately linear and does not reach saturation at 5T. It is demonstrated that the temperature at which ΔSM occurs can be tuned through subtle variations in composition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
135
4
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(152 citation statements)
references
References 26 publications
(34 reference statements)
11
135
4
2
Order By: Relevance
“…Another advantage of this alloy is that due to small hysteresis in the M (H) curve at T = 90 K, the energy loss is minimum (∼ 8 J/kg) compared to other Mn-based systems [39][40][41].…”
Section: Methodsmentioning
confidence: 99%
“…Another advantage of this alloy is that due to small hysteresis in the M (H) curve at T = 90 K, the energy loss is minimum (∼ 8 J/kg) compared to other Mn-based systems [39][40][41].…”
Section: Methodsmentioning
confidence: 99%
“…This phenomenon is corresponding with values of magnetic entropy change. is not capable of measuring the ∆T above RT but one could expect a peak value ≈1.5 2 K [7]. At RT Ni 50 Mn 18.75 Cu 6.25 Ga 25 alloy shows very low value of |∆S M | ≈ 0.7 J/(kg K) which provide temperature change of ≈0.4 K (Fig.…”
Section: The Transformation Temperaturesmentioning
confidence: 99%
“…2) gives the Curie point the nature of rst-order transition (rapid loss of magnetization) [7]. The Gd addition in Ni 50 Mn 16.75 Cu 6.25 Ga 25 Gd 2 alloy leads to separating both transition temperatures (Fig.…”
Section: The Transformation Temperaturesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that both T M and T C values are very much dependent on the composition of a particular Heusler alloy. [4][5][6][7][8][9][10][11][12][13][14][15][16] There is also another category of full Heusler alloys, which are known to be metallic for one kind of spin channel and insulator for the other kind of spin channel because of their very high spin polarization (HSP) at the Fermi level. They are often called as half metallic Heusler alloys.…”
Section: Introductionmentioning
confidence: 99%